Duchowość w świetle pozytywistycznego paradygmatu polskiego religioznawstwa końca XIX wieku - Kojkoł, Jerzy (Przegla̜d religioznawczy, 2013)
In this article we may find an analysis of the problem of spirituality in the context of positivist paradigm of the Polish study of religion by the end of 19th century. The author stresses out the fact that despite the domination of the scientistic model of science at that time the Polish study of religion did already contain some elements which were evident for its humanistic origins. Author of this article does find them in the works, basically in accordance with the positivistic and evolutionist current within the Polish study of religion by J. A. Karłowicz and I. Radliński. The author performs an analysis of their work in the context of the problem of spirituality, which in this view was a thought or a psychic act, of a inner character by its nature; it was a free thought and the link between man and the outer world, also with other people. According to the author of this article, both thinkers acknowledged the fact that myths related to the concept of soul were one of the basic elements that shape the spirituality of people. Their content was related to the level of cognition and understanding by man the biological and social reality. Spirituality in the concepts of both authors reveals itself in this article as a conscious and a social product of reason created by its relations towards the empirical limitations of an individual existing in the world, as a creation of reason and soul and our cognition revealing itself in the speech.